1980
DOI: 10.1111/j.1365-2125.1980.tb04793.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy and pharmacokinetics of conventional propranolol and a long acting preparation of propranolol.

Abstract: 1 Plasma levels of propranolol were measured at intervals after the oral administration of 160 mg propranolol and 160 mg L.A. propranolol in ten subjects who received both drugs on separate occasions.2 Mean peak plasma concentration of propranolol occurred 2 h after propranolol and 10 h after the L.A. formulation; the peak concentration with the former was four times that with the latter. At 24 h the plasma level was significantly higher after L.A. propranolol. 3 Observations were made in nine healthy voluntee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
1

Year Published

1981
1981
1993
1993

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 15 publications
7
31
1
Order By: Relevance
“…Studies with LA prppranolol have clearly shown that after 160 mg of this formulation there is a significantly greater reduction in an exercise tachycardia at 24 h than with the conventional formulation (Leahey et al, 1980a). Similar studies have shown that there is no significant difference in the effects of 160 mg oxprenolol and 160 mg SR oxprenolol on an exercise tachycardia 24 h after administration and neither produces a significant reduction in the exercise tachycardia at this time (Leahey et al, 1980b;Bobik, Jennings, Korner, Ashley & Jackman, 1979).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Studies with LA prppranolol have clearly shown that after 160 mg of this formulation there is a significantly greater reduction in an exercise tachycardia at 24 h than with the conventional formulation (Leahey et al, 1980a). Similar studies have shown that there is no significant difference in the effects of 160 mg oxprenolol and 160 mg SR oxprenolol on an exercise tachycardia 24 h after administration and neither produces a significant reduction in the exercise tachycardia at this time (Leahey et al, 1980b;Bobik, Jennings, Korner, Ashley & Jackman, 1979).…”
Section: Discussionsupporting
confidence: 51%
“…Attention has been paid recently to the administration of the total daily dose of f3-adrenoceptor blocking drugs as a single dose. The administration of propranolol as a single dose each 24 h has been shown to control arterial pressure throughout this period (Wilson, Morgan & Morgan, 1976;Douglas-Jones, Baber & Lee, 1978) but at the end of the dose interval, the degree of cardiac /8-adrenergic receptor blockade will probably be small (Leahey et al, 1980a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arthur et al (1985) examined propranolol levels in 10 cirrhotic patients who were given 160 mg daily of a long acting preparation for 7 days. A steady state was established after 3 days and levels in most patients were must higher than control data obtained from the literature (Leahey et al, 1980). In the present study detailed information on the pharmacokinetics of propranolol have been obtained by using an acute intravenous dose and two different oral doses to produce steady state.…”
Section: Discussionmentioning
confidence: 92%
“…In normal subjects a long acting preparation of propranolol that is taken once daily, has been shown to produce plasma concentrations which maintain significant 3-adrenoceptor blockade throughout the dose interval (Leahey et al, 1980 …”
Section: Introductionmentioning
confidence: 99%